2005
DOI: 10.1097/00001888-200508000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students??? Perceptions of Medical Education Research and Their Roles as Participants

Abstract: Medical school decisionmakers should recognize that students value medical education research. Published opinions about why medical students participate in studies are incongruent with medical students' views. Full review of medical education studies by Institutional Review Boards may be unnecessary and inappropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 5 publications
3
27
0
5
Order By: Relevance
“…A short questionnaire was developed based on literature review of recent articles pertaining to the topic [2,5,8,[10][11][12][13][14]. The survey is composed of four sections that fulfill our aims: a demographic section (both individual and institutional), a research involvement section, an attitudes section, and a knowledge and skills section.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…A short questionnaire was developed based on literature review of recent articles pertaining to the topic [2,5,8,[10][11][12][13][14]. The survey is composed of four sections that fulfill our aims: a demographic section (both individual and institutional), a research involvement section, an attitudes section, and a knowledge and skills section.…”
Section: Measurementmentioning
confidence: 99%
“…In each study, there is new evidence that arises pertaining to the population studied. In most cases, it seems that medical students are interested in research [8], but only a few are actually involved in the process [9]. Several reasons were reported such as the lack of time [2], the format in which the research experience was offered [10], and the lack of knowledge about the research process [11], among others.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, in a research by the Kansas City university of Medicine ninety three percent (93%) of the students felt that research improved their medical training by improving the understanding of the subject [16]. In a research work carried out to see the contrast in the ideas between novices and experienced research students it was found that, experienced students reported distinct personal, professional, and cognitive outcomes relative to their novice peers, including a more sophisticated understanding of the process of scientific research.…”
Section: Resultsmentioning
confidence: 97%
“…12 A survey of osteopathic physicians in training in 2005 found that nearly one-fourth of clinical students believed better grades, recommendations, or other favors would accompany participation in clinical trials. 13 Further concerns of professional coercion and anonymity have been raised not only with biochemical trials, but also with educational endeavors. 14 In the course of research involving residents or other trainees, sensitive information might be discovered that could be damaging to the professional future of the subject.…”
Section: Ethical Challengesmentioning
confidence: 99%